Correlation of Vocabulary Proficiency and Learning Styles with Reading Comprehension of Prospective English Teachers: A Case of Universitas Lampung - Suparman, Ujang (FKIP Universitas Lampung, 2022)
Correlation of Vocabulary Proficiency and Learninng Styles with Reading Comprehension of Prospective English Teachers: A Case of Universitas Lampung. Objectives: To analyze the correlation of vocabulary proficiency (X1) and reading achievement (Y); second, to investigate the correlation between learning styles (X2) and reading achievement (Y); and to analyze the composite correlation between X1, X2 and Y. Methods: Simple random technique was used, 80 students were chosen, out of 120, based on the total sample, i.e., all students taking reading comprehension and vocabulary. A questionaire was used to measure learning styles, and two sets of tests were used, to measure vocabulary and reading achievement. Findings: There was a correlation between students’ vocabulary proficiency (X1) and reading achievement (Y), r = 0.532; there was a correlation between learning styles (X2) and reading achievement (Y), r = 0.784; finally, there was a correlation between X1, X2 and Y, r = 0.823. Conclusion: Vocabulary proficiency and learning styles play important roles in improving reading achievement.Keywords: vocabulary proficiency, learning styles, comprehension.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202203